Synthesis of Fe3O4/PDA Nanocomposites for Osteosarcoma Magnetic Resonance Imaging and Photothermal Therapy - Zhang, Yifei; Ning, Rende; Wang, Wei; Zhou, Yejin; Chen, Yao (Frontiers in Bioengineering and Biotechnology, 2022)
Osteosarcomas commonly develop in the metaphysis of the long diaphysis, resulting in pronounced malignancy and high rates of early pulmonary metastasis. At present, osteosarcoma patients exhibit relatively poor survival rates owing to such metastasis and to the emergence of tumor resistance to chemotherapeutic treatment. As such, there is an urgent need to identify other approaches to treating affected patients. Herein, we synthesized composite Fe3O4@PDA nanocomposites that exhibited excellent biocompatibility and low toxicity in human and animal model systems. The resultant NPs were able to improve T2 magnetic resonance imaging and to enhance the signal-to-noise ratio associated with osteosarcoma tumors in animal models. Moreover, we were able to successfully leverage these Fe3O4@PDA particles as a photothermal agent capable of significantly inhibiting the growth of tumors and their metastasis to the lung compartment. Together, these results highlight a novel therapeutic platform that has the potential to guide both the more effective diagnosis and treatment of osteosarcoma patients in clinical applications.